Life and scientific activity of Charles Darwin (1809-1882) - A. V. Deforzh (History of science and technology, 2013)
Life and activity of Charles Darwin are illuminated in the article, the different forms of natural selection, substantive provisions of evolutional studies are characterized. In detail the factors of evolution are examined: struggle for existence, natural selection, artificial and antihunt selection, proofs of evolution.